2020
DOI: 10.3390/biom10081139
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activities of Selected Essential Oils

Abstract: Recently, the application of herbal medicine for the prevention and treatment of diseases has gained increasing attention. Essential oils (EOs) are generally known to exert various pharmacological effects, such as antiallergic, anticancer, anti-inflammatory, and immunomodulatory effects. Current literature involving in vitro and in vivo studies indicates the potential of various herbal essential oils as suitable immunomodulators for the alternative treatment of infectious or immune diseases. This review highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 85 publications
1
72
0
2
Order By: Relevance
“…Inflammation is a physiological response caused by an infected or injured tissue in the body. Inflammatory processes can: (i) increase the permeability of mucosal endothelial cells and the interstitium’s influx of blood leukocytes, (ii) cause the expression of cell adhesion molecules, such as vascular cell adhesion molecules (VCAM) and intercellular adhesion molecules (ICAM), (iii) upregulate the activity of several enzymes (oxygenase, peroxidase, and nitric oxide synthase) and the metabolism of arachidonic acid, and (iv) cause the release of pro-inflammatory cytokines [ 122 , 123 , 124 , 125 ].…”
Section: Main Properties Of Eosmentioning
confidence: 99%
“…Inflammation is a physiological response caused by an infected or injured tissue in the body. Inflammatory processes can: (i) increase the permeability of mucosal endothelial cells and the interstitium’s influx of blood leukocytes, (ii) cause the expression of cell adhesion molecules, such as vascular cell adhesion molecules (VCAM) and intercellular adhesion molecules (ICAM), (iii) upregulate the activity of several enzymes (oxygenase, peroxidase, and nitric oxide synthase) and the metabolism of arachidonic acid, and (iv) cause the release of pro-inflammatory cytokines [ 122 , 123 , 124 , 125 ].…”
Section: Main Properties Of Eosmentioning
confidence: 99%
“…2) and their oxygenated derivatives (alcohols, aldehydes, esters, ketones, phenols, and oxides) [13,[23][24][25]. Numerous in vitro and in vivo studies have shown that EOs and many of their individual EOCs exhibit different biological properties, for example, antibacterial [13,23,25], antifungal [13], antiviral [13], antioxidant [26,27], immunomodulatory [28,29], anti-inflammatory [24,27], and wound healing effects [30]. Due to their fat solubility, low molecular weight, and small size, the EOCs are able to pass through the skin, mucosa, and cell membranes and thus enter the systemic body circulation [13,24].…”
Section: Chemical Characteristics and Biological Effects Of Essential Oilsmentioning
confidence: 99%
“…Since antiquity, plants and their metabolites have been used for a variety of purposes in various parts of the world (Sandner et al 2020) The term "essential oil" is derived from the 16th-century Swiss reformer Paracelsus von Hohenheim's term "Quinta essential" (Wińska et al 2019). They are bioactive molecules with antibacterial/antimicrobial, antiviral, anthelmintic, antispasmodic, cytotoxic, insecticidal, anti-in ammatory, sedative, and neuroprotective properties that have all been linked to the commercial applications of EOs as avoring and preservatives in the food and agriculture industries, fragrance additives in the cosmetic industry, and antibacterial/antimicrobial properties in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 3000 plant species known to contain EOs, only 300 have been reported as commercially viable. Terpenoid mixtures (terpenes, monoterpenes, and sesquiterpenes), phenylpropenes, avonoids, esters, and unsaturated fats have been linked to the bioactive properties of essential oils (Sandner et al 2020;Greta 2020;Bahr et al 2019;Herman et al 2019). EOs are classi ed according to their extraction method (steam-distilled oils, cold-pressed/expressed oils or solvent-extracted oils) or aroma (citrus oils, herbaceous oils, oral oils, and so on).…”
Section: Introductionmentioning
confidence: 99%